2012
DOI: 10.1063/1.3687190
|View full text |Cite
|
Sign up to set email alerts
|

Silicon layer intercalation of centimeter-scale, epitaxially grown monolayer graphene on Ru(0001)

Abstract: We develop a strategy for graphene growth on Ru(0001) followed by silicon-layer intercalation that not only weakens the interaction of graphene with the metal substrate but also retains its superlative properties. This G/Si/Ru architecture, produced by silicon-layer intercalation approach (SIA), was characterized by scanning tunneling microscopy/spectroscopy and angle resolved electron photoemission spectroscopy. These experiments show high structural and electronic qualities of this new composite. The SIA all… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
94
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 22 publications
7
94
0
1
Order By: Relevance
“…[35][36][37][38] In our recent study, we reported the facile intercalation of water underneath the graphene on Ru(0001), 23 and showed that the water film decouples the first layer from the substrate. This is presented in Fig.…”
mentioning
confidence: 98%
“…[35][36][37][38] In our recent study, we reported the facile intercalation of water underneath the graphene on Ru(0001), 23 and showed that the water film decouples the first layer from the substrate. This is presented in Fig.…”
mentioning
confidence: 98%
“…Very recently, silicon, a semiconductor element, was introduced as the interfacial layer between graphene and its metallic host in the system of Gr/Ru(0001), which effectively weakens the interaction between graphene and ruthenium. 19 In this regard, silicon buffer layers play a particularly important role, since this semiconductor material makes it possible to directly insert an insulating interface between graphene and underlying metal. Such a graphene/insulator/metal heterostructure could be compatible with current microelectronic technology and provide the advantages of device integration based on largescale graphene.…”
mentioning
confidence: 99%
“…7,8 In the last few years, huge efforts have been undertaken to understand the electronic, structural, and magnetic properties of intercalated graphene systems both with and without the substrate. [9][10][11][12][13] Intercalation of Si is particularly interesting due to the fact that this material forms the basis of modern electronics technology. In addition, Si intercalated graphene systems are characterized by a particularly high stability.…”
Section: Introductionmentioning
confidence: 99%